Relationship between the pedestrian activity and physical environment in the case of Taman University, Skudai-Malaysia - Anjomshoaa, Elahe (2012)
Presence of pedestrian activities in urban environments as an important Urban Design principle that plays a vital role in the human life entails many social, environmental and economic benefits. As many experts believe there is a growing interest in understanding the influence of attributes of the built environment on habitual pedestrian activity; however, this effort on encouragement of pedestrian to walk and do activities has been failed in some cases like Taman University - Malaysia. Hence, in such environments, liveliness of urban streets would be lost, and car dependency will be encouraged. In such situation, the study of pedestrian activities in physical environment seems to be crucial. Hence, this research aims to study the possible effect of physical environment on quality and quantity of pedestrian activity in urban streets. Back to the main problem specified in this study, which highlights the importance of pedestrian activities in urban streets, following method has been used: firstly, number of pedestrian activities including Necessary, Optional and Social activities data in selected cases are recorded by ‘snapshot’ method and secondly, physical properties of space, including land use, building and street elements are quantified in selected cases. Doing this research, the main outcome of this study would point out to the significant role of commercial land uses in encouraging pedestrian activities.